2021
DOI: 10.48550/arxiv.2104.07605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SummVis: Interactive Visual Analysis of Models, Data, and Evaluation for Text Summarization

Abstract: Novel neural architectures, training strategies, and the availability of large-scale corpora haven been the driving force behind recent progress in abstractive text summarization. However, due to the black-box nature of neural models, uninformative evaluation metrics, and scarce tooling for model and data analysis, the true performance and failure modes of summarization models remain largely unknown. To address this limitation, we introduce SUMMVIS, an open-source tool for visualizing abstractive summaries tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…If a model can pinpoint which portion of a summary is inconsistent, some work has shown that corrector models can effectively re-write the problematic portions and often remove the inconsistency . Furthermore, fine-grained consistency scores can be incorporated into visual analysis tools for summarization such as SummViz (Vig et al, 2021). The SUMMAC ZS model is directly interpretable, whereas the SUMMAC Conv is slightly more opaque, due to the inability to trace back a low score to a single sentence in the document being invalidated.…”
Section: Choice Of Granularitymentioning
confidence: 99%
“…If a model can pinpoint which portion of a summary is inconsistent, some work has shown that corrector models can effectively re-write the problematic portions and often remove the inconsistency . Furthermore, fine-grained consistency scores can be incorporated into visual analysis tools for summarization such as SummViz (Vig et al, 2021). The SUMMAC ZS model is directly interpretable, whereas the SUMMAC Conv is slightly more opaque, due to the inability to trace back a low score to a single sentence in the document being invalidated.…”
Section: Choice Of Granularitymentioning
confidence: 99%
“…Sum-merTime adopts a subset of such metrics in Sum-mEval that are more popular and easier to understand. SummerTime also works well with Sum-mVis (Vig et al, 2021), which provides an interactive way of analysing summarization results on the token-level. We also allow SummerTime to store output in a format that can be directly used by SummVis and its UI.…”
Section: Existing Systems For Summarizationmentioning
confidence: 99%
“…Visualization In addition to showing the numerical results as tables, SummerTime also allows the users to visualize the differences between different models with different charts and SummVis (Vig et al, 2021). Fig.…”
Section: Model Selectionmentioning
confidence: 99%
“…Yet other methods exist for domains beyond supervised learning / classification, applied instead to unsupervised learning / clustering [19,32,68], reinforcement learning [53], AI planning [15], computer vision [91], recommendation systems [88], natural language processing [57,81,86], speech recognition [33], or multi-agent simulations [6] . Specialized XAI techniques even exist for adaptive systems such as interactive visualization systems [77], interactive virtual agents [37,83], active learning [27], and human-in-the-loop systems [86] . Furthermore, comparative studies across multiple XAI techniques have shown low mutual agreement [58], which is consistent with internal research findings at AI Research.…”
Section: The Challengesmentioning
confidence: 99%